Placing Indian Village System in the Centre of Development-Induced Displacement Discourse - Anand Prasad Mishra; Soumyabrata Mondal; Prakash Chandra Jha (European Journal of Geography)
The contemporary development process under the impact of neo-liberal policies has rapidly changed and restructured the socio-economic sphere of village life in India. The evolving pattern of rural society has turned its socio-economic structure into a complex space full of contradictions. As a result, the geographical space has been altered in terms of the representation of maps, information, and ideological interests. These spatial patterns have added to the complexities of space that have attracted scholars who relate it to new theories in developmental economics. The present paper attempts to analyse some of these aspects of the Indian rural society undergoing the process of development and displacement and its impact on different socio-economic groups, i.e., peasants, small and marginal farmers, share-croppers, artisans, agricultural labourers, and landless labourers. One-sided development, especially in the agrarian economy, disturbs the traditional skill, livelihood, and social order ultimately spreading the issues of unsustainable livelihood, hardship, and marginalization in peri-urban areas. Reskilling and participation in the decision-making process of the displaced people of developing society have become a challenging issue for policy orientation related to Development Induced Displacement (DID).